New Directions in Organizational and Management History - Coman, Sonia (De Gruyter Studies in Organizational and Management History,, 2022)
This book provides a valuable review of the disciplines of organizational and management history, illuminating the interconnectedness of these disciplines, identifying gaps in the literature, and sketching a model for a unified field of research and study. This co-authored study is a long-awaited theoretical re-evaluation of organizational and management history. The authors explore the disciplinary advantages of a joint approach to these related fields, noting opportunities for future scholarship, from the wider range of industries and case types to the richer theoretical toolbox. Within this framework, the book investigates interdisciplinary methodologies and surveys and analyzes the most promising of the newest theoretical lenses and empirical approaches in the field. The authors address complex issues from a metacritical perspective, from the emergent theorization of time in the context of organizational identity to the conundrum of case selection for empirical studies. Clear and thorough, the volume creates a compelling theoretical framework for future studies. New Directions in Organizational and Management History inaugurates, and sets the stage for, the new series De Gruyter Studies in Organizational and Management History.